A Pure 2H‐MoS2 Nanosheet‐Based Memristor with Low Power Consumption and Linear Multilevel Storage for Artificial Synapse Emulator. (22nd January 2020) - Wang, Kaiyang; Li, Liteng; Zhao, Rujie; Zhao, Jianhui; Zhou, Zhenyu; Wang, Jingjuan; Wang, Hong; Tang, Baokun; Lu, Chao; Lou, Jianzhong; Chen, Jingsheng; Yan, Xiaobing
Abstract: Two‐dimensional (2D) transition metal dichalcogenide has attracted significant attention recently due to its unique electrical and optical properties. However, MoS2 nanosheets fabricated by traditional methods exhibit poor electrical performance due to the existence of the 1T metal phase. A solution‐processable pure 2H semiconductor phase MoS2 nanosheet for use as the functional layer of high‐performance memristors is presented. The resulting memristor based on a Ag/MoS2 /Pt structure exhibits excellent resistive switching properties including high endurance and multilevel retention. Moreover, the power consumption and programming current of the SET operation can be as low as 7.35 nW and 100 nA, respectively. Interestingly, it is demonstrated that the resistance of the Ag/MoS2 /Pt device can be bidirectionally modulated over a wide range (pulse number >500) with an approximately linear trend. Furthermore, the accuracy of pattern recognition with handwritten data can reach 90.37%. This work provides a simple and practical method for the realization of fabrication of pure 2H‐MoS2 and application in biological neural computing systems. Abstract : A new technical solution dubbed the "two‐step method" is used to prepare pure 2H phase MoS2 nanosheets. The method comprises intercalation by deep eutectic solvent and exfoliation with bovine serum albumin. Additionally, a low power consumption and linear memristor with an Ag/MoS2 /Pt structure is constructed. With this device, pattern recognition accuracy based on handwritten data can reach 90.37% after 160 training iterations.